Agronomic performance and pod shattering resistance of soybean genotypes with various pod and seed colors - Ayda Krisnawati; Muchlish Adie (Society for Indonesian Biodiversity, 2021)
Abstract. Krisnawati A, Adie MM. 2021. Agronomic performance and pod shattering resistance of soybean genotypes with various pod and seed colors. Biodiversitas 22: 474-481. Climate change impacts agricultural production, including the increase of the yield loss in soybean due to pod shattering. This research aimed to identify the pod shattering resistance and agronomic performance of several soybean genotypes with various pod and seed colors. A total of 100 soybean genotypes were planted in Malang (East Java, Indonesia) during the dry season 2019. The field experiment was laid out in a randomized block design with three replications. The pod shattering resistance was assessed using the oven-dry method. The pod shattering resistance of 97 genotypes were classified into 20 very resistant genotypes, 17 resistant genotypes, 15 moderate genotypes, nine susceptible, and 36 very susceptible genotypes. The pod colors did not affect the pod shattering resistance in soybean. The new findings from this study, i.e., two very resistant genotypes (G42 and G15) which produce high yield and have medium maturity, were suggested to be developed as new cultivars, meanwhile, the other very resistant genotypes can be used in the soybean breeding program to develop shattering resistant cultivar with desirable traits.